AN ANALYSIS OF GRAMMATICAL ERROR IN WRITING PERSONAL LETTERS - Taufik Afdal; Joko Iswanto; Ririn Dwi Riana (Universitas Negeri Islam Sumatera Utara, 2022)
The study aims to discover the grammatical errors made by students when writing personal letters. The indicators are sentence pattern error, tense error, pronoun error, preposition error, and punctuation error. The researcher would be able to determine the types of errors that students made in their writings based on these indicators. The descriptive qualitative method was used in this study. The students were from SMK Negeri 1 Bintan Timur's class XI. The Samples consisted of 13 students. The samples were collected using total sampling by the researcher. The instrument was performing a test. In conclusion, the results revealed that each student made an error in each indicator. And the most common error made by students was an error in Sentence Pattern, which accounted for 37% of all errors. And the lowest error is in Pronoun by 19%. Keywords: Grammatical Error ; Writing ; Personal Letter